The Influence of the Grammar Translation Method and the Direct Method on Students’ Results - Kącka-Stanik, Iwona (Respectus Philologicus, 2016)
It is believed that the way teacher introduces new material is directly connected with students’ results. Due to that fact, teachers are advised to choose the method that will help the students absorb the new material efficiently and at the same time in a pleasant way. Some of the teachers tend to use the grammartranslation method and translate every word into the mother tongue. However, there are also such teachers who tend to introduce the new material with the help of direct method. They only use target languageand teach children communication. Teachers have always wondered which method is better, more attractive to students and more effective when it comes to the learners’ progress and test results. This article presents theoretical background connected with teaching children. The theoretical issues concern teaching in general, the description of two methods used while introducing the new material as well as types of techniques used in the grammar-translation and direct method. To sum up, it can be concluded that there is a connection between the method the teacher uses to introduce new material and students’ results. The results of the study explain the significance of choosing the right method. Due to that fact, the teachers are recommended to use the direct method to keep the learners interested and motivated.